2013
DOI: 10.1364/ol.38.004182
|View full text |Cite
|
Sign up to set email alerts
|

Low-haze light extraction from organic light-emitting diode lighting with auxiliary electrode by selective microlens arrays

Abstract: Improved out-coupling efficiency and low haze of organic light-emitting diode (OLED) lighting with an auxiliary electrode are demonstrated by selective microlens arrays (SMLAs). The microlens arrays, aligned with the auxiliary electrode, were selectively fabricated, since the fully packed microlens arrays lead to OLED lighting with high haze. The external quantum efficiency and power efficiency of the devices with the SMLAs increased by 32% when compared with the devices without these arrays. Using the SMLAs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…As with the grid width control, the optical transmittance was linearly related to the opening area of the metallic grid electrode. We additionally measured the haze (total diffusion/total transmittance) at 550 nm of the grid electrodes as shown in SI Figure S3, which is superior to the previously reported values of silver nanowire electrodes. The sheet resistance increased with the grid spacing, giving a resistance of 67 Ω/sq for a 40 μm grid spacing or 128 Ω/sq for a 200 μm spacing, but unfortunately, large mismatches between the calculated and experimental values were observed for grid spacings of less than 150 μm. Higher values of the measured sheet resistance may incorporate two effects: A PS residue may remain on the metal grid lines after RIE etching, or the metallic line may partially disconnect due to the thin grid width of 4.5 μm.…”
Section: Resultsmentioning
confidence: 85%
“…As with the grid width control, the optical transmittance was linearly related to the opening area of the metallic grid electrode. We additionally measured the haze (total diffusion/total transmittance) at 550 nm of the grid electrodes as shown in SI Figure S3, which is superior to the previously reported values of silver nanowire electrodes. The sheet resistance increased with the grid spacing, giving a resistance of 67 Ω/sq for a 40 μm grid spacing or 128 Ω/sq for a 200 μm spacing, but unfortunately, large mismatches between the calculated and experimental values were observed for grid spacings of less than 150 μm. Higher values of the measured sheet resistance may incorporate two effects: A PS residue may remain on the metal grid lines after RIE etching, or the metallic line may partially disconnect due to the thin grid width of 4.5 μm.…”
Section: Resultsmentioning
confidence: 85%
“…With a structure similar to OLEDs, the LEE of QLEDs is significantly limited due to reflection from the glass‐air interface. It has been previously demonstrated that photonic crystal nanostructures can be used above the glass surface for enhancing the LEE of an OLED device where the trapped light within the QLED escapes into the air as a result of Bragg diffraction and scattering from the nanostructures on the glass surface . Among them, ZnO nanostructures are promising materials as light outcoupling medium because of their high index and excellent optical transparency as well as easy solution fabrication process .…”
Section: Resultsmentioning
confidence: 99%
“…etal halide perovskite light-emitting diodes (PeLEDs) reveal the advantages over organic light-emitting diodes (OLEDs) due to their outstanding optoelectronic characteristics, such as excellent color purity [1], high brightness [2], and tunable luminescence [3][4][5] etc., which are very suitable for the promising applications covering the general lighting to next-generation flatpanel displays [6]- [7]. There has been considerable amount of research and development for the improvement of efficiency through incorporation of various nanostructures into PeLEDs, for instance, the nanopatterns on transparent substrate (destroy substrate mode [8]- [9]), surface texture and roughness (utilize diffraction effect [10][11][12]), metallic nanostructures (enhance light-matter interaction by plasmonic effect [13][14][15]) and photonic crystals (manipulate light by Bloch mode [16]). The reported external quantum efficiencies of red, green and blue PeLEDs have substantially improved to 20%, 20%, 10%, respectively [17].…”
Section: Introductionmentioning
confidence: 99%